2024
DOI: 10.1371/journal.pone.0296068
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of pulmonary arteries and lung tissues from dogs affected with pulmonary hypertension secondary to degenerative mitral valve disease

Siriwan Sakarin,
Anudep Rungsipipat,
Sittiruk Roytrakul
et al.

Abstract: In dogs with degenerative mitral valve disease (DMVD), pulmonary hypertension (PH) is a common complication characterized by abnormally elevated pulmonary arterial pressure (PAP). Pulmonary arterial remodeling is the histopathological changes of pulmonary artery that has been recognized in PH. The underlying mechanisms that cause this arterial remodeling are poorly understood. This study aimed to perform shotgun proteomics to investigate changes in protein expression in pulmonary arteries and lung tissues of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…It has been indicated that the appearance of PVH in dogs with left heart failure leads to a significant decrease in the synthesis of bcl-2-like protein 4 (BAX), caspase-3, and caspase-8 proteins (pro-apoptotic proteins) and an increase in the expression of anti-apoptotic B-cell lymphoma-2 (BCL-2) [45]. Proteomic studies, in dogs with MMVD and PVH, revealed an increase in the synthesis of apoptosis resistance proteins and the progression of medial thickening [57]. The study detected the proteins whose changes were most significant: up-regulation of salt-induced kinase 3 (SIK3), collagen type I alpha chain 1 (COL1A1), and transforming growth factor alpha (TGF-α) and down-regulation of apoptosis-associated tyrosine kinase (AATYK), hepatocyte growth factor activator (HGFA) and non-receptor protein tyrosine phosphatase type 13 (PTPN13) [57].…”
Section: Pulmonary Vesselsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been indicated that the appearance of PVH in dogs with left heart failure leads to a significant decrease in the synthesis of bcl-2-like protein 4 (BAX), caspase-3, and caspase-8 proteins (pro-apoptotic proteins) and an increase in the expression of anti-apoptotic B-cell lymphoma-2 (BCL-2) [45]. Proteomic studies, in dogs with MMVD and PVH, revealed an increase in the synthesis of apoptosis resistance proteins and the progression of medial thickening [57]. The study detected the proteins whose changes were most significant: up-regulation of salt-induced kinase 3 (SIK3), collagen type I alpha chain 1 (COL1A1), and transforming growth factor alpha (TGF-α) and down-regulation of apoptosis-associated tyrosine kinase (AATYK), hepatocyte growth factor activator (HGFA) and non-receptor protein tyrosine phosphatase type 13 (PTPN13) [57].…”
Section: Pulmonary Vesselsmentioning
confidence: 99%
“…Proteomic studies, in dogs with MMVD and PVH, revealed an increase in the synthesis of apoptosis resistance proteins and the progression of medial thickening [57]. The study detected the proteins whose changes were most significant: up-regulation of salt-induced kinase 3 (SIK3), collagen type I alpha chain 1 (COL1A1), and transforming growth factor alpha (TGF-α) and down-regulation of apoptosis-associated tyrosine kinase (AATYK), hepatocyte growth factor activator (HGFA) and non-receptor protein tyrosine phosphatase type 13 (PTPN13) [57]. The SIK family of proteins is one of the regulators of myocardial inflammation and fibrosis through the activation of apoptosis signal-regulating kinase 1 (ASK1) [58,59].…”
Section: Pulmonary Vesselsmentioning
confidence: 99%
See 1 more Smart Citation